(untitled) (Docentes 2.0 Journal, 2020)
Technological resources have allowed the incursion of interactive or non-interactive digital tools in education, strengthening the learning of students in different areas of knowledge, however, in the “Dr. Juan Henríquez Coello”, Ecuador, high school students have shortcomings during the teaching-learning process, in the computer science subject. For this reason, the present study, raised as research objective; the design of a Virtual Learning Object to strengthen the essential basic learning of high school students, this being a prototype that arises as part of the COVA project proposed at the Technical University of Machala. Within the methodology, participatory action research was used, in addition to using the questionnaire as data collection instruments together with a survey based on the Likert scale allowing to know the degree of satisfaction, as well as the attitude of the 60 high school students who they used the digital resource. Among the results, it was possible to show the proposal of the Virtual Learning Object, where the students demonstrated a positive attitude towards the proposed resource, obtaining an acceptance of 90% by the participants. Finally, it is necessary to mention the use of the ADDIE methodology as a fundamental guide for the construction and implementation of a Virtual Learning Object allowing to propose the OVA as a digital educational resource for interaction between the teacher - student, strengthening the teaching-learning process of the study contents of a subject.